Phase transformation induces plasticity with negligible damage in ceria-stabilized zirconia-based ceramics. (15th January 2020) - Liens, Aléthéa; Reveron, Helen; Douillard, Thierry; Blanchard, Nicholas; Lughi, Vanni; Sergo, Valter; Laquai, René; Müller, Bernd R.; Bruno, Giovanni; Schomer, Sven; Fürderer, Tobias; Adolfsson, Erik; et al.
Abstract: Ceramics and their composites are in general brittle materials because they are predominantly made up of ionic and covalent bonds that avoid dislocation motion at room temperature. However, a remarkable ductile behavior has been observed on newly developed 11 mol.% ceria-stabilized zirconia (11Ce-TZP) composite containing fine alumina (8 vol.% Al2 O3 ) and elongated strontium hexa-aluminate (8 vol.% SrAl12 O19 ) grains. The as-synthesized composite also has shown full resistance to Low Temperature Degradation (LTD), relatively high strength and exceptionally high Weibull modulus, allowing its use in a broader range of biomedical applications. In this study, to deepen the understanding of plastic deformation in Ce-TZP based composites that could soon be used for manufacturing dental implants, different mechanical tests were applied on the material, followed by complete microstructural characterization. Distinct from pure Ce-TZP material or other zirconia-based ceramics developed in the past, the material here studied can be permanently strained without affecting the Young modulus, indicating that the ductile response of tested samples cannot be associated to damage occurrence. This ductility is related to the stress-induced tetragonal to monoclinic ( t-m ) zirconia phase transformation, analogue to Transformation-Induced Plasticity (TRIP) steels, where retained austenite is transformed to martensite. The aim of this study is to corroborate if the observed plasticity can be associated exclusively to the zirconia t-m phase transformation, or also to microcraking induced by the transformation. The t-m transformed-zones produced after bending and biaxial tests were examined by X-ray refraction and SEM/TEM coupled with Raman. The results revealed that the observed elastic-plastic behavior occurs without extensive microcracking, confirming a purely elastic-plastic behavior driven by the phase transformation (absence of damage). Graphical abstract: Image, graphical abstract